2018
DOI: 10.1080/13691058.2017.1421707
|View full text |Cite
|
Sign up to set email alerts
|

Addressing social and gender norms to improve uptake of maternal health services in Mali: a descriptive study of CARE’s Project Hope for Mothers and Newborns (PEMN)

Abstract: This study examines the design and implementation of a maternal mortality prevention intervention in central Mali. It uses Project Hope for Mothers and Newborns (PEMN) as a case study to examine the context around implementation, with special emphasis on the role of social, gender and power norms in meeting programme objectives. Interventions to strengthen the health system and workforce were coupled with a social norms change approach to catalyse the personal transformation of staff, community-level health wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…This is particularly important for LLMC where healthcare services utilization is still very low, and influenced by many factors. Some of these are dysfunctional and underperforming healthcare systems (Abosse et al 2010), community norms (Kuzara et al 2018), roads and transportation (Tegegne et al 2018), and key socio-demographic factors such as lower-socio-economic condition, lack of education, and not being engaged in employment (Gupta et al 2014;WHO 2015). Given the higher prevalence of unintended pregnancy in LLMC, in this study we found that ensuring maternal healthcare services utilization among women experiencing an unintended pregnancy is another important challenge.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important for LLMC where healthcare services utilization is still very low, and influenced by many factors. Some of these are dysfunctional and underperforming healthcare systems (Abosse et al 2010), community norms (Kuzara et al 2018), roads and transportation (Tegegne et al 2018), and key socio-demographic factors such as lower-socio-economic condition, lack of education, and not being engaged in employment (Gupta et al 2014;WHO 2015). Given the higher prevalence of unintended pregnancy in LLMC, in this study we found that ensuring maternal healthcare services utilization among women experiencing an unintended pregnancy is another important challenge.…”
Section: Discussionmentioning
confidence: 99%